Pengaruh Perbedaan Waktu Setting Jaring Insang terhadap Hasil Tangkapan Ikan Kembung (Rastelliger Sp.) di Perairan Pati Jawa Tengah - Lhabib Dzakwan Darojat; M. Tajuddin Noor; Exist Saraswati (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2025)
One of the fishing tools that is widely used by fishermen in the Pati waters of Central Java is the gill net. This tool has relatively higher productivity and efficiency compared to several other fishing tools because it can catch large numbers of fish when operated. It is one of the fishing tools that is environmentally friendly and popular to use because its operation is not too complicated and is good for development. The purpose of this Field Work Practice is to determine the effect of operational time of gill net fishing equipment on mackerel fish catches in. This Field Work Practice also aims to determine gill net operational times for mackerel fish catches. Data was obtained by conducting experiments from two different treatments, each treatment was repeated 16 times to obtain a total of 32 data. The research method used is the experimental fishing method using t-test analysis, homogeneity test, normality test. The results of the T-test on 16 repetitions at 07.00-10.00 WIB and 15.00-18.00 WIB were with an average amount of 205.7 kg and 244.4 kg so that a sign (2-tailed) result of 0.004 < 0.05 could be obtained. From the results of the T-test, it can be concluded that H0 is rejected and H1 is accepted, meaning that there is an average difference between the results of tagkapan at 07.00-10.00 WIB and 15.00-18.00 WIB which is influenced by several factors. So it can be concluded that differences in gill net operational times have an effect on mackerel fish. The fishing operation time of 15.00-18.00 WIB is the best operational time compared to 07.00-10.00 WIB which is caused by oceanographic factors, technical factors and natural factors.